Correlation between degree of crystallinity, morphology and mechanical properties of PPS/carbon fiber laminates - Batista, Natassia Lona [UNESP]; Olivier, Philippe; Bernhart, Gerard; Rezende, Mirabel Cerqueira; Botelho, Edson Cocchieri [UNESP] (FapUNIFESP (SciELO), 2016)
The crystallization degree in semi-crystalline thermoplastics plays an important role in determining the final properties of structural composite material (e.g. Toughness, stiffness and solvent resistance). The main purpose of this work is to study different induced degrees of crystallinity in carbon fiber (CF) reinforced polyphenylene sulfide (PPS) composites, by using three different cooling rates during hot compression molding processing (51%, 58% and 62% of crystallinity). In this study, the morphology, thermal and mechanical properties of the produced laminates were investigated and compared. The results showed an increase in the storage modulus (9.8%), Young's modulus (9.2%) and ILSS (14.2%) for the lower cooling rates. Evidences of fiber/interface improvement and crystallites nucleation on the fiber reinforcement surface were also identified.
Keywords: CF/PPS; Crystallinity; Thermoplastic composites